Proceso de atención de enfermería en paciente con insuficiencia renal etapa v en diálisis peritoneal - Briones Ortiz, Jean Carlos (2019)
Chronic renal failure is a prevalent disease at different points of public health. In the following clinical case we will describe the situation of a 68-year-old patient with a medical diagnosis of chronic kidney disease stage v in the peritoneal dialysis program, presenting a frequent complication in the peritoneal dialysis process. In the development of this topic, both the disease and the patient's medical history will be exposed, giving as an option a plan of care that allows studying and evaluating the different interventions that allow improving the patient's quality of life.